Analisis Komprehensif Strategi Indofood Selama Pandemi Covid-19 - sarjono, haryadi sarjono; Amanda Saphira; Xyla Taqiyya Wahyudi; Jang Jae Hyeok (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2025)
The COVID-19 pandemic has presented unprecedented challenges to industries worldwide, requiring agile and adaptive strategies to survive and thrive. The purpose of this study is to investigate Indofood’s strategic response to the complex landscape of the pandemic era, focusing on Crisis Management, Continuity Planning, and Strategic Sustainability (CCS). Through a comprehensive literature review, this study develops hypotheses to understand how Indofood navigated the crisis and sustained its operations. Using qualitative research methods, including financial analysis, market assessment, and supply chain evaluation, this study uncovers the complex dynamics of Indofood’s strategic changes. The results describe key performance indicators, such as revenue growth, market share, and supply chain resilience, which provide quantitative insights into the company’s resilience during the pandemic. The discussion interprets the findings in the context of existing literature, providing an in-depth understanding of Indofood’s strategic decisions. The calculated increase in net profit margin provides a comprehensive representation of Indofood’s strategy and performance during the challenging pandemic. The company’s financial resilience, market strategy, operational efficiency, and ability to adapt to rapid supply chain changes underscore its ability to successfully navigate uncertainties. This horizon serves as a valuable benchmark for stakeholders, contributing to a deeper interpretation of Indofood's response to the global crisis.